Synthetic Organic Electrochemistry: An Enabling and Innately Sustainable Method - Horn, Evan J. (ACS Cent Sci, 2016)
[Image: see text] While preparative electrolysis of organic molecules has been an active area of research over the past century, modern synthetic chemists have generally been reluctant to adopt this technology. In fact, electrochemical methods possess many benefits over traditional reagent-based transformations, such as high functional group tolerance, mild conditions, and innate scalability and sustainability. In this Outlook we highlight illustrative examples of electrochemical reactions in the context of the synthesis of complex molecules, showcasing the intrinsic benefits of electrochemical reactions versus traditional reagent-based approaches. Our hope is that this field will soon see widespread adoption in the synthetic community.